2021
DOI: 10.32920/ryerson.14652567
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hypercoordinated oxazoline and ethyl pyridyl organotin compounds: potential routes to stable polystannanes

Desiree Bender

Abstract: Tetraorganotin chelating tin (IV) compounds containing a rigid (10) and a semi-flexible (18) oxazoline ligand were synthesized by a reaction between the lithiated oxazoline and Ph3SnCl in good yields. Conversion into their corresponding dihalide species by reaction with two equivalents of bromine was undertaken to yield the dibromide species, 13 and 20 respectively. X-ray crystallography of these compounds revealed relatively short tin-nitrogen bond distances (10:2.762 13: 2.383, 18: 3.234 Å). These all fall w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Unpublished worked by a previous student, demonstrated the solid-state structure of compound 7 by obtaining a crystal suitable for single crystal x-ray diffraction. 46 It was found that there were two unique molecules of 7 within the unit cell, slightly different in bond lengths and angles (Figure 39a, c). This was compared to the optimized structures of the two conformers of 7…”
Section: Conductivity Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Unpublished worked by a previous student, demonstrated the solid-state structure of compound 7 by obtaining a crystal suitable for single crystal x-ray diffraction. 46 It was found that there were two unique molecules of 7 within the unit cell, slightly different in bond lengths and angles (Figure 39a, c). This was compared to the optimized structures of the two conformers of 7…”
Section: Conductivity Studiesmentioning
confidence: 99%
“…The dibromide stannane intermediate, 7, was synthesized according to unpublished work by Desiree Bender. 46 This was achieved via bromination with the dropwise addition of 2 molar equivalents of Br2 to a solution of 2 in C6H6 at 0 ℃ (Scheme 11). Compound 7 was preferentially synthesized through bromination reaction rather than chlorination because upon reaction with 1.0 M solution of HCl/Et2O, the result is an insoluble product, which is most likely the formation of a salt formed via the protonation of the nitrogen atom of the pyridine ring.…”
Section: Synthesis and Characterization Of 2-(2-(dibromo(phenyl)stann...mentioning
confidence: 99%
See 1 more Smart Citation